Predictors of weight loss and maintenance in patients treated with antiobesity drugs - Guaraldi F (Dove Medical Press, 2011)
Federica Guaraldi1, Uberto Pagotto2, Renato Pasquali21Department of Pathology, The Johns Hopkins University School of Medicine, Baltimore, MD, USA; 2Division of Endocrinology, Department of Clinical Medicine, S Orsola-Malpighi Hospital, Alma Mater Studiorum University, Bologna, ItalyBackground: The prevalence of obesity and related diseases has increased enormously in the last few decades, becoming a very important medical and social issue. Because of the increasing number of people who need weight loss therapies and the high costs associated with these, the search for reliable predictors of success for weight loss and weight maintenance treatments has become a priority.Objective: A literature review was undertaken to identify possible predictors of outcome of weight loss and weight maintenance in patients treated with antiobesity drugs.Results: For the majority of variables, published data are not sufficient to define their role on final outcomes. Among all considered factors, only early response to treatment appeared to be a reliable positive predictor, and diabetes a negative predictor of weight loss and maintenance.Conclusion: To date, no definitive results have been obtained. Due to the great benefits of reliable predictors of outcome associated to currently available antiobesity drugs and those under development, identifying these predictors has to be supported and encouraged.Keywords: obesity, weight loss predictors, pharmacological treatment